(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Irrigation water quality refers to water suitability for agricultural purpose. Good water quality has the possibilities to allow maximum yield of crops under good soil and water administration practices. Ikose River water which they are using for irrigation purposes by the rural communities was evaluated for its quality. Water samples were collected in dry as well as rainy season into sterilized, labelled bottles and were transported in ice pack to laboratory for analyses. Results were pH range of 6.36-6.43, calcium (Ca2+) 23-25 mg/L, magnesium (Mg2+) 8-12 mg/L, potassium (K+) 2.40–2.50 mg/L, sodium (Na+)1.74-1.90 mg/L, bicarbonate (HC03-) 200-230 mg/L-, phosphate (PO3-P) 0.10-0.12 mg/L, electrical conductivity (EC) is within 0.06 mg/L, Nitrate (NO3-N) 0.04–0.42 mg/L, sulphate (SO42-) 24-25 mg/L, total dissolved (TDS) 28.70-30.20 mg/L for the dry season and the pH ranged from 7.01-7.03, (Ca2+) 45-48 mg/L, (Mg2+) 24-18 mg/L, (K+) 4.20–4.30 mg/L, (Na+) 2.12-2.14 mg/L, (HCO-3) 350-360 mg/L, (PO3-P) 0.19-0.20 mg/L, (EC) is within 0.11 mg/L, (NO3-N) 0.10-0.11 mg/L, (SO42-) 38.00-39.00 mg/L, (TDS) 54.50-54.60 mg/L for the rainy season. The samples analyzed were within the recommended standard limits set for irrigation water quality. The water quality indicators MAR, 29.4; SAR,0.08; SSP,3.78; KR,0.04; PS, 0.46; PI, 92.95; RSC,1.46; TH, 101.5 for dry season and MAR, 36.11; SAR, 0.06; SSP, 2.03; KR, 0.02; PS,0.28; PI, 54.94; RSC, 1.36; TH, 224.5 for rainy season were under safe limits.